2009
DOI: 10.1097/jcp.0b013e3181befa3e
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Patients' Knowledge of the Adverse Effects of Psychotropic Medication and the Perceived Influence of Adverse Effects on Compliance Among Service Users Attending Community Mental Health Services

Abstract: Physicians and information leaflets are the leading sources of patients' knowledge about adverse effects of medication. The knowledge of adverse effects of medication has a potential to affect compliance, and so it is essential for physicians to engage patients in a fuller communication about their illness and its treatment with medication including the management of potential adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Before patients are initiated on CFTR modulators, pharmacists can provide the necessary counseling and education. Patients who are informed about potential AEs in advance may be more willing to trial a new medication [123,124], especially if strategies to address potential AEs are provided [123]. Anecdotally, this has been true at our site: some patients have expressed hesitancy and concern about potential AEs secondary to CFTR modulators, but once monitoring and strategies to address potential AE were discussed, they were more open to a trial.…”
Section: Patient Counseling and Educationmentioning
confidence: 99%
“…Before patients are initiated on CFTR modulators, pharmacists can provide the necessary counseling and education. Patients who are informed about potential AEs in advance may be more willing to trial a new medication [123,124], especially if strategies to address potential AEs are provided [123]. Anecdotally, this has been true at our site: some patients have expressed hesitancy and concern about potential AEs secondary to CFTR modulators, but once monitoring and strategies to address potential AE were discussed, they were more open to a trial.…”
Section: Patient Counseling and Educationmentioning
confidence: 99%
“…Lack of such knowledge is widespread and a prevailing source of dissatisfaction among patients with BD[75,101,106,113,127,128]. Patients appear particularly unhappy with the lack of information provided on side effects and other aspects related to medication-treatment[75,86,127-129]. Although enhancing knowledge should improve adherence among patients, results of studies in BD have been somewhat equivocal in this regard.…”
Section: Patient-centred Determinants Of Non-adherence In Bdmentioning
confidence: 99%
“…10,14,17,18 Patients are looking for information, [19][20][21][22][23][24][25][26][27][28] particularly about adverse effects. [29][30][31][32][33] However, studies have shown that physicians provide little information regarding pharmacological treatments. [34][35][36][37][38] According to the patient medication-taking practice model developed by Bajcar, making "sense of the purpose" of the medication is of significant importance for adherence.…”
Section: Introductionmentioning
confidence: 99%